2016
DOI: 10.7567/apex.9.042701
|View full text |Cite
|
Sign up to set email alerts
|

Passively Q-switched erbium-doped fiber laser using Fe3O4-nanoparticle saturable absorber

Abstract: Received Month X, XXXX; revised Month X, XXXX; accepted Month X, XXXX; posted Month X, XXXX (Doc. ID XXXXX); published Month X, XXXX We experimentally demonstrate a passively Q-switched erbium-doped fiber laser (EDFL) operation by using a saturable absorber based on Fe 3 O 4 nanoparticles (FONP) in magnetic fluid (MF). As a kind of transition metal oxide, the FONP has a large nonlinear optical response with a fast response time for saturable absorber. By depositing MF at the end of optical fiber ferrule, we fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…Previous work shows that Fe 3 O 4 nanoparticles possess a large third-order optical nonlinearity, semi-conductive property, and size-dependent bandgap [39][40][41][42]. Based on a two-level model for semi-conductive materials [26,46], the nonlinear absorption property can be described as follows: under low incident power, the absorption of such nanoparticles is independent of the laser intensity.…”
Section: Experiments Results and Dicussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work shows that Fe 3 O 4 nanoparticles possess a large third-order optical nonlinearity, semi-conductive property, and size-dependent bandgap [39][40][41][42]. Based on a two-level model for semi-conductive materials [26,46], the nonlinear absorption property can be described as follows: under low incident power, the absorption of such nanoparticles is independent of the laser intensity.…”
Section: Experiments Results and Dicussionmentioning
confidence: 99%
“…Recently, several groups have demonstrated that Fe 3 O 4 nanoparticles display a semi-conductive property, and the bandgap can be tuned by controlling their sizes [41]. Such nanoparticles possess a large third-order optical nonlinearity, semi-conductive property, and size-dependent bandgap, which satisfies the saturable absorption condition and thus can be used as a Q-switcher in lasers [42].…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of enhancing power resistance, these SAs have evolved from traditional semiconductor saturable absorber mirrors (SESAMs) [3] to one-dimensional and twodimensional materials, such as carbon nanotubes [4][5][6], graphene [7][8][9][10][11], black phosphorous [12][13][14][15], and transition-metal dichalcogenides (TMDs) [16][17][18][19][20]. Quite recently, it has been demonstrated that another novel material group of zero-dimension transition metal oxides (TMOs) including TiO 2 , ZnO, Al 2 O 3 and Fe 3 O 4 possesses efficient nonlinear SA properties [21][22][23][24][25][26][27][28]. Compared with carbon nanotubes and other two-dimension materials, the prepared zero-dimension nanomaterials-based SA is more uniform due to their smaller lateral size and regular circle-like shape [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, it has been demonstrated that another novel material group of zero-dimension transition metal oxides (TMOs) including TiO 2 , ZnO, Al 2 O 3 and Fe 3 O 4 possesses efficient nonlinear SA properties [21][22][23][24][25][26][27][28]. Compared with carbon nanotubes and other two-dimension materials, the prepared zero-dimension nanomaterials-based SA is more uniform due to their smaller lateral size and regular circle-like shape [24][25][26]. Among the TMOs, Fe 3 O 4 is an attractive nanomaterial due to large third-order nonlinear susceptibility of 4.0 × 10 −10 esu and a high nonlinear optical absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation